2008
DOI: 10.1677/erc-07-0092
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral concentration of sex steroids and expression of sex steroid-producing enzymes in ductal carcinoma in situ of human breast

Abstract: It is well known that sex steroids play important roles in the development of invasive ductal carcinoma (IDC) of the human breast. However, biological significance of sex steroids remains largely unclear in ductal carcinoma in situ (DCIS), regarded as a precursor lesion of IDC, which is partly due to the fact that the intratumoral concentration of sex steroids has not been examined in DCIS. Therefore, in this study, we first examined the intratumoral concentrations of estradiol and 5a-dihydrotestosterone (DHT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…For example, the mean concentration of E2 in the breast tumors of premenopausal patients was approximately 1.2 pmol/g tissue (that means that if the density of tumor is 2 g/mL, the in situ E2 concentration will be 2.4 nmol/L), whereas a plasma E2 concentration of approximately 0.22 nmol/L was reported in the same paper [4,5] . Similar results were obtained from other previous studies [6,7] and from our current study on MCF-7 xenograft tumors (0.36-0.48 nmol/L). However, we once investigated the effect of TM208 on SULT1A1 and SULT2A1 and found that TM208 induced the expression of SULT1A1 more significantly than that of SULT2A1 in both MCF-7 cells and MCF-7 xenograft tumors, but all of the observed increases were less than 4-fold (Figure S1-S2).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For example, the mean concentration of E2 in the breast tumors of premenopausal patients was approximately 1.2 pmol/g tissue (that means that if the density of tumor is 2 g/mL, the in situ E2 concentration will be 2.4 nmol/L), whereas a plasma E2 concentration of approximately 0.22 nmol/L was reported in the same paper [4,5] . Similar results were obtained from other previous studies [6,7] and from our current study on MCF-7 xenograft tumors (0.36-0.48 nmol/L). However, we once investigated the effect of TM208 on SULT1A1 and SULT2A1 and found that TM208 induced the expression of SULT1A1 more significantly than that of SULT2A1 in both MCF-7 cells and MCF-7 xenograft tumors, but all of the observed increases were less than 4-fold (Figure S1-S2).…”
Section: Discussionsupporting
confidence: 92%
“…These data are neither significantly different from each other nor from the E2 level in the normal mammary fat pad (0.39±0.01 nmol/L). The absolute reduced intratumoral E2 concentration in the TM208 treatment group is not as much as the levels observed in situ for the human breasts of healthy women versus patients [4,6,7] , but the difference was statistically significant, and all the tested concentrations were within the physiological range of E2 concentration. To the best of our knowledge, we are the first group to detect the intratumoral E2 concentration in MCF-7 xenograft mice.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Other researchers found similar data, with significant aromatase activity ranging from 52 to 72 percent in invasive carcinoma samples. [3][4][5][6][8][9][10] As for studies that tried to assess aromatase enzyme expression in DCIS, there seems to be discrepancies in the literature. Aromatase expression analyses in 61 cases of pure DCIS found higher rates than for 101 cases of IDC.…”
Section: Discussionmentioning
confidence: 99%